2018
DOI: 10.1002/nafm.10070
|View full text |Cite
|
Sign up to set email alerts
|

Quantile Regression Estimates of Body Weight at Length in Walleye

Abstract: Quantile regression is a method of estimating fish weight at length for alternate portions of a probability distribution, but it is an approach that has not received much attention in fisheries literature. Quantile regression can provide estimates of any quantile of weight at length without bias (including the 75th quantile, which was often the focus of standard weight [Ws] equations), and this is more advantageous than previously defined Ws equations derived from linear or quadratic regression methods. The go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
(87 reference statements)
1
5
0
Order By: Relevance
“…As in previous studies of fish body condition that involved the use of quantile regression (Cade et al 2008(Cade et al , 2011Crane et al 2015;Crane and Farrell 2017;Ranney 2018), we found extensive variation in the allometric exponents used to estimate weight at length of Arctic Grayling and consequent heterogeneity in the predicted distributions of weights at length. The percentile summaries that we used to partition distributions of weight at length from quantile predictions into quartiles constitute a simple device for collapsing predicted quantiles from many levels of a grouping factor (here, locations or years) to provide a more concise summary for comparative or diagnostic purposes.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…As in previous studies of fish body condition that involved the use of quantile regression (Cade et al 2008(Cade et al , 2011Crane et al 2015;Crane and Farrell 2017;Ranney 2018), we found extensive variation in the allometric exponents used to estimate weight at length of Arctic Grayling and consequent heterogeneity in the predicted distributions of weights at length. The percentile summaries that we used to partition distributions of weight at length from quantile predictions into quartiles constitute a simple device for collapsing predicted quantiles from many levels of a grouping factor (here, locations or years) to provide a more concise summary for comparative or diagnostic purposes.…”
Section: Discussionsupporting
confidence: 72%
“…Quantile regression estimates in linear models with any relevant grouping factors or continuous covariates provide a much more comprehensive and rigorous analysis of changes in weight at length, and there are multiple recent examples demonstrating this capability for fish condition analyses (Cade et al 2008(Cade et al , 2011Crane et al 2015;Crane and Farrell 2017;Ranney 2018;Neely et al 2021;Woodward et al 2021). Our percentile summary approach provides a method by which to concisely summarize estimates across multiple levels of a grouping factor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, when weight data are unavailable from the field, species‐specific length–weight regression formulas are used to generate weight data (Gerow, Anderson‐ Sprecher, & Hubert, 2005; Murphy, Brown, & Springer, 1990). Unfortunately, morphological variability both among fish and seasonally for individual fish can further reduce the precision of calculated weight estimates (Adams, Leaf, Wu, & Hernandez, 2018; Neumann & Murphy, 1992; Ranney, 2018). Finally, the time and effort required to obtain length and weight measurements in the field imposes limitations on the number of fish that can be sampled; which reduces the confidence in data capturing individual variability (Gutreuter & Krzoska, 1994).…”
Section: Introductionmentioning
confidence: 99%